The Bangladesh parliament : a data handbook - Ahmed, Nizam; BRAC University. Institute of Governance Studies; International Development Research Centre (IDRC); Centre de recherches pour le developpement international (CRDI) (Dhaka : Institute of Governance Studies, BRAC University, 2013)
All about Bangladesh national parliament, its history, structure, functions; its success and failure from 1973 to 2011.
Includes bibliographical references (pages [405]-413).
Keywords: Bangladesh. -- Jātīẏa Saṃsada; Bangladesh -- Politics and government -- 1971- -- Statistics